A Statewide Effort to Implement Collaborative Care for Depression: Reach and Impact for All Patients With Depression. Issue 11 (November 2016) - Rossom, Rebecca C.; Solberg, Leif I.; Parker, Emily D.; Crain, A. Lauren; Whitebird, Robin; Maciosek, Michael; Molitor, Beth; Trangle, Michael; Unützer, Jürgen
Abstract : Background: Little is known about the reach and impact of collaborative care for depression outside of clinical trials. Objective: The objective of this study was to examine the effect of a collaborative care intervention for depression on the rates of depression diagnosis, use of specific depression codes, and treatment intensification. Research Design: Evaluation of a staggered, multiple baseline implementation initiative. Subjects: Patients receiving depression care in primary care clinics throughout Minnesota from February 2008 through March 2011. Measures: Data regarding depression diagnosis rates and codes, and measures of antidepressant intensification were provided by health insurers. Results: Depression Improvement Across Minnesota: Offering a New Direction (DIAMOND) affected neither rates of depression recognition nor use of depression diagnostic codes, and the overall reach of DIAMOND was disappointingly small. Patients in DIAMOND had more episodes of treatment intensification than non-DIAMOND patients, but we were unable to account for depression severity in our analysis. Conclusions: DIAMOND did not affect depression recognition or diagnostic coding, but may have affected treatment intensification. Our results suggest that even strongly evidence-based interventions may have little contamination effects on patients not enrolled in the new care model.